Japan in the Early Modern World: Religion, Translation, and Transnational Relations - Jolliffe, Pia (Übersetzungskulturen der Frühen Neuzeit J.B. Metzler Humanities (German Language), 2025)
Open Access. Early modern transnational relations and personal encounters were influenced by interactions between Japan and the regions that had become connected to it through expanding global trade and missionary networks. Translation activities linked to Christian missionary activities, overseas trade, and political upheaval in these places all contributed to shaping these interactions. Adopting an interdisciplinary perspective, this volume explores religion, translation, and transnational relations in the context of the colonial and missionary enterprises involving Japan, between 1550 and 1800. It focuses on the early Catholic mission to Japan, discussing both Protestant and local religious reactions to it, and the publications of the Jesuit mission press in Japan. A survey of the subsequent centuries of scholarly involvement with translational materials in Asian languages further suggests that translation had a formative influence on the intellectual world in the Early Modern period